Screening of antifungal potentials of Lactobacillus helveticus KLDS 1.8701 against spoilage microorganism and their effects on physicochemical properties and shelf life of fermented soybean milk during preservation. (August 2016) - Bian, Xin; Muhammad, Zafarullah; Evivie, Smith Etareri; Luo, Guang-Wen; Xu, Min; Huo, Gui-Cheng
Abstract: This study investigated the screening of antifungal potential of Lactobacillus helveticus . L. helveticus KLDS 1.8701 showed strongest antifungal activity against Penicillium sp. of all provided strains, and antifungal activity was from organic acids and KLDS 1.8701 itself. Results of the impact of KLDS1.8701 on spoilage microorganisms in fermented soybean milk during the preservation period showed that it could inhibit Penicillium sp. and other spoilage microorganisms from the environment and the shelf-life of products were extended. The addition of KLDS 1.8701 has no significant effect on biochemical, rheological and sensory properties of fermented soybean milk. It also enhances total viable counts of Lactobacillus stains ( L. helveticus + Lactobacillus bulgaricus )and didn't affect Streptococcus thermophiles . Thus, the use of L. helveticus KLDS 1.8701 as a bio-protective culture in other fermented products was suggested. Highlights: L. helveticus KLDS1.8701 shows strongest antifungal activity against Penicillium. Antifungal activity was from organic acids and KLDS 1.8701 itself. KLDS 1.8701 could extend the shelf-life of fermented soybean milk. The addition of KLDS 1.8701 has no effect on properties of fermented soybean milk.